LEVEL OF SALMONELLA IN BEEF OF SLAUGHTERED CATTLE AT PESHAWAR - M. Aftab; A. Rahman; M. S. Qureshi; S. Akhter; U. Sadique; A. Sajid; S. Zaman (Journal of Animal and Plant Sciences, 2012)
A research study was designed to find out the level of Salmonella contamination on cattle body coat, fresh carcasses, beef after transportation and display at butcher shops. The animals were divided into two groups i.e. washed and unwashed animals. Salmonella was found in 100 % samples. A log total viable count was significantly (P < 0.001) higher in unwashed samples as compared with washed (22.33±0.088 and 19.54±0.09) respectively. Carcasses samples from unwashed animals had significantly (P < 0.001) higher log total viable count of Salmonella (24.45± 0.06) as compared with washed animals (21.77± 0.05). Results suggested that samples collection after 6-7 hours display at shop showed higher degree of Salmonella contamination and the isolation was significantly affected by duration and washing of the samples. Abattoir floor has higher (30.36±0.08) Salmonella contamination, followed by chopper axe (22.14± 0.05) and knives (15.14± 0.09). It is concluded from the result that Salmonella prevalence was reduced in all stages of the slaughtering operations by washing with Luke warm water. However, it is recommended that washing with some sanitizer will eliminate the pathogen from body coat thus resulting in little chances of beef contamination.
Keywords: Meat; Salmonella; Contamination; Cattle; Abattoir; Khyber Pakhtun Khwa